Design of a Portable Non-Contact Body Temperature Measurement Device Based on Arduino - Desriyanti; Francisco Ade Fristanto; Muhammad Zainuri; Yunan Sepda Kurnyanda; Rizka, Rizka Yuliana (Diagnosa, 2026)
Advances in electronic instrumentation have enabled the development of digital health monitoring systems. During the COVID-19 pandemic, non-contact body temperature measurement became crucial to reduce physical contact and minimize the risk of virus transmission, as conventional contact-based thermometers present hygiene limitations and are inefficient for mass screening. This study designs and develops a portable non-contact body temperature measurement device based on Arduino Uno. The system utilizes an MLX90614 infrared temperature sensor to measure body temperature without direct contact. Temperature data are processed by the microcontroller and displayed in real time on an OLED screen, with a push button for measurement control and a battery as a portable power source. The experimental results show that the developed system is able to measure body temperature accurately and consistently within an acceptable error range. The MLX90614 sensor exhibits a fast response time, and the OLED display provides clear real-time temperature readings. All system components operate reliably and are well integrated. The proposed Arduino-based portable non-contact body temperature measurement device functions effectively and is suitable for health screening applications. The system offers a practical, safe, and hygienic solution for body temperature monitoring, with potential for further improvements through calibration enhancement and IoT-based integration.